Kemampuan Guru Dalam Pemanfaatan Media Pembelajaran Sederhana Sebagai Sumber Belajar - Nur Azima; Gustina Kusuma Dewi; Siska Amalia; Inevsha Cornellya; Wismanto Wismanto (Lembag, 2024)
The development of science and technology requires high quality human resources capable of responding to various challenges. Therefore, education must always be considered and prioritized in order to produce quality human resources. As an important part of successful learning, teachers must be able to position themselves as people who can instill a love of learning in their students. The aim of this research is to encourage the use of learning media in conveying learning messages and helping students better understand the learning process. The type of field study in this case uses a qualitative approach. The method used in this research is a descriptive qualitative method with a library research approach. The main data used in this research comes from books, magazines and recent articles related to the theme of this research. The results of this research show that: (1) teachers have access to simple learning media in formats from various sources that can be used as teaching materials, (2) design simple learning media that is as attractive as possible by using used teaching materials such as plastic bottles, leaves, twigs in the environment. school, and (3) the classroom as a place where teachers play a role during learning and carrying out the learning process, the introduction of simple learning media applied in the school yard, and the surrounding community environment.